Catalyzing green finance a concept for leveraging blended finance for green development. - Mehta, Anouj (Metro Manila, Philippines Asian Development Bank, 2017)
A large financing need challenges climate adjusted infrastructure in developing Asia, estimated at 26 trillion till 2030. This necessitates crowding in private sources to meet financing, efficiency, and technology gaps. However, a lack of bankable projects is a major hurdle. This publication suggests one possible innovative financing approach. The Green Finance Catalyzing Facility (GFCF) proposes a blended finance framework for governments and development entities to better leverage development funds for risk mitigation, generate a pipeline of bankable green infrastructure projects, and directly catalyze private finance. The GFCF provides useful inputs for the current debate on mainstreaming green finance into country financial systems.
Keywords: Environmental economics; Finance -- Environmental aspects; Environmental policy; Sustainable development -- Finance; Climate change mitigation -- Economic aspects; Electronic books